A Shear Wall Design Study in an 8-Story Building - Teddy, Livian; Tumbelaka, Hanny Hosiana (Journal of Architectural Design and Urbanism, 2025)
Indonesia is an earthquake-prone region. These natural disasters have caused buildings to collapse and claimed many lives, highlighting the need for earthquake-resistant design. Faculty of Engineering (FE) of Universitas Sriwijaya plan to build an earthquake-resistant 8-story building functioning as classrooms and office. The problem is how to determine the appropriate structural system between SMRF alone or a combined SMRF-SRCSW system and how to determine the optimal position of the shear wall without disturbing the existing layout in the FE Tower.This research method employed a simulation experiment using six models of FE Tower. The Model was analyzed using software to obtain fundamental vibration period, mode shape, soft story check, torsional irregularity check, and the concrete structure design analysis.Software analysis results indicate that the FE Tower exhibits both vertical and horizontal geometric irregularities, necessitating dilatation for simplification. The structural system used in this design combines SMRF and SRCSW, and the optimal position of the shear wall is positioned on the outer wall and corner of the building.